Malignant Transformation of Endometriosis: An Unusual Diverticular Mass. Issue 2 (April 2016) - Mohling, Shanti I.; Elkattah, Rayan; Eliason, Rachel; Boren, Todd P.
Background: Malignant transformation of endometriosis may occur years following hysterectomy and oophorectomy. It may present with a pelvic mass, pain or vaginal bleeding. Risk factors have been poorly defined, but may include exogenous or endogenous unopposed estrogens. Case: This report presents a case of malignant transformation of endometriosis resulting in endometrioid adenocarcinoma of a colonic diverticulum in a patient on unopposed estrogen. Conclusions: Patients with a history of endometriosis who present with a pelvic mass should be evaluated for the possibility of a tumor arising from the endometriosis, even long after definitive surgical treatment. Sampson's criteria for malignant transformation of endometriosis remain relevant. The continued practice of prescribing unopposed estrogen after hysterectomy to patients with a history of endometriosis may contribute to the frequency of this otherwise uncommon disease.